The Effect of Social Privilege on Cognitive Empathy Among University Students in Indonesia - Puji Rahayu; Zainuddin, Nurul Inayah; Almuttasim, Ananda Akhirianti (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
This study examines the effect of social privilege on cognitive empathy among university students in Indonesia. Using a quantitative correlational design, data were collected from 309 students enrolled in public and private universities across diverse socio-cultural regions. The instruments employed were the Privilege and Oppression Inventory (POI) and the Perspective Taking subscale of the Interpersonal Reactivity Index (IRI). Data were analyzed using simple linear regression. The results indicate a positive but weak relationship between social privilege and cognitive empathy. The regression coefficient (β = 0.10, p = 0.08) suggests that social privilege does not significantly predict cognitive empathy. Consistently, the coefficient of determination (R² = 0.010) shows that social privilege accounts for only 1% of the variance in cognitive empathy, with most variation explained by other psychosocial and contextual factors. These findings suggest that cognitive empathy among university students is shaped more by social interactions and educational experiences than by structural advantage alone. The study underscores the importance of character education and campus policies that foster inclusive learning environments and meaningful cross-group interactions to support empathy development in higher education. This research contributes to discussions on empathy, social inequality, and student development in diverse academic contexts.